Effects of Acute Prolonged Sitting and Interrupting Prolonged Sitting on Heart Rate Variability and Heart Rate in Adults: A Meta-Analysis - Bates, Lauren C.; Alansare, Abdullah; Gibbs, Bethany Barone; Hanson, Erik D.; Stoner, Lee (Frontiers in Physiology, 2021)
The primary objective was to quantify heart rate (HR) and variability (HRV) responses to prolonged sitting. A secondary objective was to investigate changes in HR or HRV after interrupting prolonged sitting (e.g., walking). Electronic databases were searched (inception-August 2020) for studies which exposed adults to prolonged (≥1 hour) sitting with and/or without interruptions. Twenty-one articles (27 trials, n=537) met inclusion criteria. Prolonged sitting non-significantly affected HR (weighted mean difference (WMD)=0.27 bpm, 95% CI: -2.15, 2.69) and HRV (standardized mean difference (SMD)= 0.12, 95% CI: -0.08, 0.33). Interrupting prolonged sitting yielded a small increase in HR (WMD=3.64 bpm, 95% CI: -0.04, 7.31). An insufficient number of trials were available to quantify sitting interruptions on HRV. Sub-group analyses investigating interrupting prolonged sitting revealed small-to-moderate increases in HR in healthy populations (WMD=5.64 bpm, 95% CI: 1.45, 9.82), females (WMD=6.97 bpm, 95% CI: 1.91, 12.03), ≥ 4-hour sitting (WMD=4.65 bpm, 95% CI: 1.27, 8.02), and walking interruptions (WMD=6.87 bpm, 95% CI: 2.77, 10.97). In conclusion, prolonged sitting does not significantly affect HR or HRV. Thus, sitting may not increase the risk of poor cardiovascular outcomes via autonomic disruption. However, interrupting prolonged sitting yielded a small increase in HR, potentially indicative of increased metabolic demand.